Antinociceptive, anti-inflammatory and antipyretic properties of an aqueous extract of Corchorus capsularis leaves in experimental animal models. - Zakaria, Zainul Amiruddin; Kumar, Gunjan Hanan; Raden Mohd Nor, Raden Nur Suraya; Sulaiman, Mohd Roslan; Abdullah, Fatimah Corazon; Mat Jais, Abdul Manan; Somchit, Muhammad Nazrul; Ismail, Maznah (Informa Healthcare, 2009)
The present study was carried out to establish the antinociceptive, anti-inflammatory and antipyretic properties of an aqueous extract of jute plant leaves, Corchorus capsularis L. (Tiliaceae), in experimental animals. The antinociceptive activity was measured using the abdominal constriction, hot plate and formalin tests, while the anti-inflammatory and antipyretic activities were measured using the carrageenan-induced paw edema and brewer's yeast-induced pyrexia tests, respectively. The extract, obtained after 72 h soaking of the air-dried leaves in distilled water, freeze-drying for 72 h and then prepared in dosages of 11.57, 57.85, and 115.7 mg/kg, was administered subcutaneously (10 ml/kg) 30 min prior to subjection to the above mentioned assays. The extract was found to exhibit significant (antinociceptive, anti-inflammatory and anti-pyretic, activities in a dosage-independent manner. In conclusion, the aqueous extract of C. capsularis possesses antinociceptive and antipyretic activities and supports the previous claim of its traditional use to treat various ailments.